A Novel Hypothesis: A Role for Follicle Stimulating Hormone in Abdominal Aortic Aneurysm Development in Postmenopausal Women - Tedjawirja, Victoria N.; Nieuwdorp, Max; Yeung, Kak Khee; Balm, Ron; de Waard, Vivian (Frontiers in Endocrinology, 2021)
An abdominal aortic aneurysm (AAA) is a dilatation of the abdominal aorta, which can potentially be fatal due to exsanguination following rupture. Although AAA is less prevalent in women, women with AAA have a more severe AAA progression compared to men as reflected by enhanced aneurysm growth rates and a higher rupture risk. Women are diagnosed with AAA at an older age than men, and in line with increased osteoporosis and cardiovascular events, the delayed AAA onset has been attributed to the reduction of the protective effect of oestrogens during the menopausal transition. However, new insights have shown that a high follicle stimulating hormone (FSH) level during menopause may also play a key role in those diseases. In this report we hypothesize that FSH may aggravate AAA development and progression in postmenopausal women via a direct and/or indirect role, promoting aorta pathology. Since FSH receptors (FSHR) are reported on many other cell types than granulosa cells in the ovaries, it is feasible that FSH stimulation of FSHR-bearing cells such as aortic endothelial cells or inflammatory cells, could promote AAA formation directly. Indirectly, AAA progression may be influenced by an FSH-mediated increase in osteoporosis, which is associated with aortic calcification. Also, an FSH-mediated decrease in cholesterol uptake by the liver and an increase in cholesterol biosynthesis will increase the cholesterol level in the circulation, and subsequently promote aortic atherosclerosis and inflammation. Lastly, FSH-induced adipogenesis may lead to obesity-mediated dysfunction of the microvasculature of the aorta and/or modulation of the periaortic adipose tissue. Thus the long term increased plasma FSH levels during the menopausal transition may contribute to enhanced AAA disease in menopausal women and could be a potential novel target for treatment to lower AAA-related events in women.